Synthesis, Characterization and Antimicrobial Activityof 3-substituted Benzo[4,5]thiazolo[2,3-c][1,2,4]triazole - Rafah F. Al-Smaism; Ayad M.R. Raauf; Basma M. Abd Razik; Hala A.M. Rasheed (College of Pharmacy / Mustansiriyah University, 2013)
New series of tricyclic benzo[d]thiazole derivatives (2-12) incorporated into fused to different five membered nitrogen and sulphur containing heterocyclic were prepared from 2- hydrazinobenzo[d]thiazole (1) when treated with triethylformate, acetic anhydride, ethyl chloro acetate, carbon disulphide in alkali, and urea respectively. Compound(1) converted to Schiff's bases by the condensation different aromatic aldehydes, the synthesized Schiff's bases were cyclized by bromine in acetic acid to form triazole ring in the new derivatives (7-11) , which might result in biologically active agents. Similar new tricyclic compounds, triazolobenzothiazol-3-amine [12], was obtained from action of benzo[d]thiazole-2-thiol with thiosemicarbazide. The structures of the new compounds have been characterized by elemental analysis and spectral data. Newly synthesized compounds (2-12) were screened for their antibacterial activity against four bacterial species. They were found to exhibit good antibacterial activity.